Mechanisms and structures to support and accompany start-ups ANSEJ، ANGEM، CNAC، ANDI - شريفي نورة (International Journal of Social Communication, 2025)
Start-ups are considered an effective development alternative if given attention, given the role they play in economic development by creating mechanisms and structures to support and accompany these institutions, given their importance in increasing job opportunities, creating added value, and developing exports. We will try in This study highlights the most prominent national bodies supporting start-ups in Algeria, as well as some pioneering international experiences in activating economic development programs and upgrading these institutions by creating several bodies and funds to develop and advance them by studying four national bodies: the Agency ANGEM, CNAC Agency.ANDI We relied in our study on the descriptive analytical approach based on analysis and inference. The SPSS program was used to analyze the data. The study concluded that have been able to absorb part of the unemployment rate in Tlemcen and attract a significant proportion of the total job opportunities due to their advantages, which makes relying on them the best option to drive the wheel of economic development